A EFFECT OF COMBINATION OF CONCENTRATION OF TURMERIC EXTRACT (Curcuma longa L.) AND SUGAR ON WATER CURRENT AND ORGANOLEPTIC JELLY CANDY - Maghfiroh Khoirin (Journal of Natural Sciences and Learning, 2023)
Jelly candy is made from gelling agents and essences to produce a variety of flavors, a clear transparent appearance, and a chewy texture. In general, jelly candy uses gelatin as its gelling agent. Doubts about the halalness of gelatine make research into the potential of other gelling agents necessary. Carrageenan can replace gelatin as a gelling agent because of its gelling ability. This study used turmeric extract as a colorant for jelly candy. This study aimed to determine the effect of adding sugar and turmeric extract on the water content and organoleptic of turmeric jelly candy (Curcuma longa L.). This study used a completely randomized design with two factors: variations in sugar concentration (25%, 75%) and turmeric extract (5%, 10%, 15%). The results showed that the combination of turmeric (C. longa) extract concentration significantly affected water content; the greater the concentration of sugar and turmeric extract affected the color and taste of jelly candy. The concentration of carrageenan and konjac mixture that the panelists most liked was 75% sugar. Meanwhile, the concentration of turmeric extract that the panelists most liked was the addition of 10% turmeric extract.